Training and Development of University Teachers: Role of Academic Staff College - Singh, Rohit; Singh, Rajesh Kumar (Prabandhan: Indian Journal of Management, 2010)
The 21st century has rightly placed Human Resources at the top and proved that it only can give 'competitive edge' to the organizations. It is important that the human resources are put in use effectively. It is the only resource which gets depleted when not in use. Hence, it becomes mandatory to sharpen the skills to use it effectively. Training and development is a process by which teachers in various groups are helped to acquire new set of competent skills continuously so as to make them more and more self reliant and simultaneously develop a sense of pride in their community. It is a known fact that ASC of various universities serves as a role model in every sphere of its activities. Training and Development is a life long process for every human being, particularly for those in academia. University Grants Commission, AICTE and Ministry of Human Resource Development takes primary responsibility in organizing various Orientation Programs, Principal Workshops and Refresher Courses recommended by the Expert Committee for Academic Staff Colleges, Technical institutes and colleges.